Pembuatan Perangkat Ajar Kurikulum Merdeka Melalui Pendekatan Understanding By Design Bagi Guru IPS Madrasah di Kabupaten Rejang Lebong - Muhammad Ilham Gilang; Nurniswah Nurniswah (UIN Fatmawati Sukarno Bengkulu, 2024)
This research aims to describe the ability of Madrasah Social Sciences teachers in Rejang Lebong Regency in understanding the Independent Curriculum and creating teaching tools. This research was conducted at eight schools/madrasas consisting of; (1) MAN Rejang Lebong, (2) MA Baitul Makmur, (3) MA Muhammadiyah, (4) SMK Quran Darul Maarif NU, (5) MTs Baitul Makmur, (6) MTs Muhammadiyah, (7) MTs Bunayah, and ( 8) Darul Maarif NU Quran Middle School. This target represents elements of State Transfer Madrasas, Private Aliyah Madrasas, Private Tsanawiyah Madrasas, Private Middle Schools, NU Mass Organization-based Middle Schools and Muhammadiyah-based MTs. The research questions are (1) What is the initial state of understanding of madrasa social studies teachers in Rejang Lebong Regency regarding the Independent Curriculum Understanding By Design before training?, (2) What is the training process for social studies teachers in creating teaching tools for the Independent Curriculum based on Understanding By Design? , (3) What is the final state of understanding of madrasa social studies teachers in Rejang Lebong Regency regarding the Independent Understanding By Design Curriculum after the training? The research method is Participatory Action Research (PAR), which is an approach to solving problems and meeting the practical needs of society, as well as producing knowledge, and encouraging social and religious change. The results of the research show that firstly, the initial condition of the madrasah social studies teachers before the training showed a lack of understanding regarding the material regarding the Independent Curriculum, both philosophically, conceptually, technically, and the steps in carrying out social studies learning in the classroom. Marked by not being able to mention the Teaching Module as a replacement for the RPP in the Independent Curriculum. Second, the training process for social studies teachers in making teaching tools for the Independent Curriculum based on Understanding By Design is conveyed by teachers gaining new understanding, new skills, and training that can be used to make teaching tools. Third, the state of understanding of madrasa social studies teachers in Rejang Lebong Regency regarding the Independent Understanding By Design Curriculum after the training shows changes in attitudes after the training, and is useful in solving existing social problems.